2014
DOI: 10.1177/1932296813519882
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of a Novel Embedded Closed-loop System

Abstract: Despite significant improvements in the care of type 1 diabetes, achieving tight glycemic control while avoiding hypoglycemia 1,2 remains a challenge for many patients and novel therapeutic approaches are required. Closed-loop insulin delivery is an emerging treatment option for patients with type 1 diabetes. 3 Compared to preprogrammed basal insulin rates in insulin pumps, closed-loop insulin delivery systems modulate insulin delivery in glucose-responsive fashion based on subcutaneous sensor glucose levels u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…This value is higher than the 4% reported by Reddy et al and the 11% reported by Kovatchev et al in previous adult inpatient short‐term studies. Overnight, the reference time in the range of 3.9 to 10.0 mmol/L was 83% with Diabeloop, a value similar to the 82% to 90% values previously reported The reduction in average glucose reported in the present study (1.0 mmol/L) compares well with the 0.3 to 2.1 mmol/L reduction observed by others …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This value is higher than the 4% reported by Reddy et al and the 11% reported by Kovatchev et al in previous adult inpatient short‐term studies. Overnight, the reference time in the range of 3.9 to 10.0 mmol/L was 83% with Diabeloop, a value similar to the 82% to 90% values previously reported The reduction in average glucose reported in the present study (1.0 mmol/L) compares well with the 0.3 to 2.1 mmol/L reduction observed by others …”
Section: Discussionsupporting
confidence: 92%
“…This value is higher than the 4% reported by Reddy et al 38 and the 11% reported by Kovatchev et al 20 in previous adult inpatient short-term studies. Overnight, the reference time in the range of 3.9 to 10.0 mmol/L was 83% with Diabeloop, a value similar tothe 82% to 90% values previously reported [20][21][22].…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The pathway to the use of consumer electronics to perform medical functions is discussed in recent FDA guidance [30], which defines medical mobile applications and the process of their regulatory approval. The Medtronic 530G insulin pump with a low glucose suspend feature provides some of the safety features of a full artificial pancreas system and several research groups [31,32], have conducted AP clinical trials with smartphone or purpose-built portable systems. A comprehensive discussion of the current status of artificial pancreas systems is presented in [33].…”
Section: Introductionmentioning
confidence: 99%